Nonlinear waves in heterogeneous elastic rods via homogenization - Quezada de Luna, M; Đuričković, B; Goriely, A (2011)
We consider the propagation of a planar loop on a heterogeneous elastic rod with a periodic microstructure consisting of two alternating homogeneous regions with different material properties. The analysis is carried out using a second-order homogenization theory based on a multiple scale asymptotic expansion.